CANON EOS R10 pocket guide : buttons, dials, settings, modes, and shooting tips. (ROCKY NOOK, 2023)
Designed for photographers who haven't memorized every button, dial, setting, and feature on their Canon EOS R10, Rocky Nook's handy and ultra-portable quick reference Pocket Guide helps you get the shot when you're out and about. • Confirm that your camera is set up properly with the pre-shoot checklist • Identify every button and dial on your camera • Learn the essential modes and settings you need to know • Dive deeper with additional features of your camera • Execute step-by-step instructions for shooting in-camera multiple exposures, HDR images, and time-lapse movies • Follow tips and techniques for getting great shots in typical scenarios (portrait, landscape, freezing action, low light, etc.).